1984
DOI: 10.1056/nejm198402093100601
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Suppressor T Lymphocytes in the Tropical Splenomegaly Syndrome

Abstract: To study the pathogenesis of tropical splenomegaly syndrome, we compared immunologic findings in patients from Flores, Indonesia, with those obtained in local residents without splenomegaly and in controls. Villagers with tropical splenomegaly syndrome had markedly elevated levels of total IgM, higher titers of IgM antibodies to Plasmodium vivax, and reduced levels of circulating T lymphocytes. The latter were caused by a decrease in the total number of T cells with the suppressor/cytotoxic phenotype (T8+). Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

1985
1985
2002
2002

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 7 publications
2
21
0
2
Order By: Relevance
“…Wadee is the recipient of a fellowship from the South African Research Council. Address reprint requests to Dr. Piessens at the Harvard School of Public Health. Received for publication 21 September 1984 and in revised form 6 February 1985. munoregulatory thymus-dependent (T) lymphocytes in peripheral blood of patients with TSS, a finding that is consistent with this hypothesis (5). However, these studies failed to document that such phenotypic changes resulted in functional abnormalities that could account for the marked hyperproduction of IgM in patients with TSS.…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…Wadee is the recipient of a fellowship from the South African Research Council. Address reprint requests to Dr. Piessens at the Harvard School of Public Health. Received for publication 21 September 1984 and in revised form 6 February 1985. munoregulatory thymus-dependent (T) lymphocytes in peripheral blood of patients with TSS, a finding that is consistent with this hypothesis (5). However, these studies failed to document that such phenotypic changes resulted in functional abnormalities that could account for the marked hyperproduction of IgM in patients with TSS.…”
Section: Introductionsupporting
confidence: 65%
“…This observation has prompted the hypothesis that the polyclonal gammopathy of TSS results from hyperproduction of immunoglobulins (mostly IgM) by B lymphocytes activated by malarial antigens or mitogens. This, in turn, is believed to reflect an imbalance in the number and/or activity of immunoregulatory T lymphocytes in patients with this syndrome (4,5). In a previous study, we found that Indonesian patients with TSS lacked circulatory lymphocytes of the T8' (suppressor/cytotoxic) phenotype (5 Although our studies indicate that actual destruction of suppressor cells may contribute to the immunoregulatory abnormalities associated with TSS, we cannot rule out the possibility that the anti-T cell antibodies that we describe could operate in vivo by noncytotoxic mechanisms, e.g., by altering lymphocyte traffic or homing patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations